Current trends in the consumer behaviour towards eco-friendly products - Agnieszka Lorek (Economic and Environmental Studies (E&ES), 2015)
Research on environmental liability issues were already taken in the 70s and 80s, when relatively few consumers were aware of the impact of products and services on the environment. Currently, "green consumption" (sustainable consumption) is a term commonly known and an important element of the "green consumerism" has become creating environmentally friendly consumption patterns. The main purpose of the article is to identification of current trends in the consumer behaviour towards "green" products on example of Silesian Voivodeship. In the first part of the article are presented trends in consumer behaviour on a green market in developed countries. The second part relates to the identification of consumer behaviour in relation to environmental goods and services in the Silesian province on the basis of surveys. Surveys were conducted among residents of the region in 1999/2000 and 2012/2014. The above analyses indicate that the trend to make purchase decisions based on ecological criteria is diminishing. The price is still the main criterion the respondents consider when shopping (above 80% of survey participants). An important motive for buying eco-friendly products are savings associated with using energy-efficient appliances. Currently, 37% of respondents declares buying organic food and the most important criterion in all rounds of the survey are health benefits. A positive tendency was observed with regard to the post-consumer waste management (according to the survey, waste is currently segregated in most households in Silesian Voivodeship) but significantly decreased the number of people repairing broken electronic equipment and appliances which contributes to increasing the quantity of such waste.
Keywords: Q01; 330; consumer behavior; green consumption; eco-friendly products; green market; Silesian Voivodeship